Sustainable Oral Care: Analyzing the Environmental Impact of Replaceable Toothbrush Bristles - Ravikant Nanwatkar; Aniket Badhe; Yash Kakade; Sarthak Deshmane; Sandesh Dhukte (International Journal of Environmental Noise and Pollution Control, 2025)
The global rise in plastic waste has highlighted the urgent need for sustainable practices in everyday consumer products, including oral care. This study investigates the environmental impact of replaceable toothbrush bristles as an alternative to fully disposable toothbrushes. By adopting a life cycle assessment (LCA) approach, we compare the material usage, production energy, and waste generation of traditional toothbrushes with modular designs featuring reusable handles and replaceable bristle heads. The analysis reveals significant reductions in plastic consumption and waste, alongside potential energy savings during manufacturing. Consumer adoption trends and challenges are also explored through surveys and market analysis, emphasizing the importance of awareness and accessibility in driving change. The findings underscore the role of innovative product design in promoting sustainability, providing actionable insights for manufacturers, policymakers, and consumers aiming to minimize environmental footprints in oral hygiene. This research advocates for a shift toward modular toothbrush systems as a practical step toward achieving sustainable oral care practices globally.
Keywords: Environmental impact; Life Cycle Assessment; oral care; plastic waste; replaceable bristle heads